A benchmark for room acoustical simulation. Concept and database. (May 2021) - Brinkmann, Fabian; Aspöck, Lukas; Ackermann, David; Opdam, Rob; Vorländer, Michael; Weinzierl, Stefan
Abstract: Room acoustical simulations are usually evaluated by comparing them to measurements in corresponding physical environments as a benchmark. However, it proved to be challenging to provide a precise representation of the room geometry, the source and receiver characteristics, and the absorption and scattering coefficients to be re-modeled in the simulation. We aim to overcome these shortcomings by providing a database that can serve as a Benchmark for Room Acoustical Simulations (BRAS) and which is expandable and permanently available to researchers and developers of simulation software. The database includes a selection of reference scenes such as "single reflection", or "diffraction around an infinite wedge" which isolate specific acoustic phenomena. This article introduces the concept of the BRAS along with the description of the currently contained acoustic scenes and discusses the implication of measurement errors. The acquisition of impulse responses for omnidirectional and binaural receivers, the identification of the boundary conditions, and the data structure is detailed in the database itself. The BRAS is publicly available 1 . The free license under which it is provided allows for future extensions such as additional scenes or improved data due to advanced measurement techniques.